Lithium ion secondary battery
By using the two-layer structure of the negative electrode active layer in lithium-ion batteries and the 1,3,6-hexanetrinitrile in the electrolyte, the problem of poor battery circulation capacity retention is solved, and the cycle stability and magnification of the battery are improved. Performance, extending battery life.
Patent Information
- Application Number
- CN202411425072.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-10
AI Technical Summary
The poor retention rate of the cycle capacity of lithium-ion batteries leads to insufficient performance in terms of high discharge power and short charging time.
A two-layer structure of a negative electrode active layer is adopted, wherein the first active layer is pure graphite, the second active layer contains silicon carbon, and 1,3,6-hexane trinitrile is added to the electrolyte to form a stable and uniform interface through optimization. The positive electrode interface mask reduces metal ion dissolution and side reactions, and improves the cycle stability and life of the battery.
It significantly improves the circulation capacity retention rate and high temperature stability of lithium-ion batteries, extends the service life of the battery, reduces the damage to the electrode interface impedance and material structure, and enhances the rate performance and energy density of the battery.
Smart Images

Figure CN119297405A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of battery technology, and in particular relates to a lithium ion secondary battery. Background Art
[0002] In order to meet the requirements of long battery life, short charging time, and high discharge power of lithium-ion batteries, lithium-ion batteries need to further improve their energy density and charge and discharge performance.
[0003] The gram capacity of silicon is about 10 times that of traditional graphite materials, which can greatly increase the energy density of batteries. Therefore, silicon materials have been widely used in the negative electrode active material.
[0004] However, adding silicon to the negative electrode will cause the potential of the negative electrode to increase, which in turn will increase the potential of the positive electrode, leading to easy dissolution of metal elements in the positive electrode active material and increased side reactions of the electrolyte, resulting in poor battery cycle capacity retention. Summary of the invention
[0005] Therefore, the technical problem to be solved by the present invention is to overcome the defect of poor cycle capacity retention rate of batteries in the prior art and provide a lithium ion secondary battery.
[0006] To this end, the present invention provides the following technical solutions.
[0007] The present invention provides a lithium ion secondary battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator;
[0008] The negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer arranged on the negative electrode current collector, the negative electrode active layer comprises a first active layer and a second active layer, the second active layer is arranged on a surface of the first active layer away from the current collector; the first active layer comprises a first negative electrode active material, and the first negative electrode active material comprises a first graphite;
[0009] The second active layer includes a second negative electrode active material, and the second negative electrode active material includes silicon carbon;
[0010] The electrolyte comprises 1,3,6-hexane trinitrile, and the mass percentage of 1,3,6-hexane trinitrile in the electrolyte is 0.5% to 10%.
[0011] The silicon carbon comprises a porous carbon substrate, silicon dispersed in the porous carbon pores, and a carbon coating layer located on the surface of the porous carbon substrate.
[0012] In a possible implementation, the particle size D of the active material in the negative electrode active layer is V 50 is L1, the average particle size of silicon carbon in the second active layer is L2, and the O / I value of the second active layer is Z, which satisfies the following relationship:
[0013] 16 ≥ Z / (L1-L2) ≥ 1;
[0014] Preferably, the range of L1 is: 8 to 18 μm;
[0015] L2 range: 6-15 μm;
[0016] The range of Z is 8 to 30.
[0017] In a possible implementation, the second negative electrode active material further includes a second graphite, the second graphite of the second negative electrode active material includes secondary particles, and the first graphite of the first negative electrode active material includes secondary particles and unagglomerated primary particles;
[0018] Secondary particles are formed by the agglomeration of primary particles.
[0019] Preferably, the particle size of the secondary particles is Dv50=10-20 μm;
[0020] Preferably, the particle size of the primary particles is Dv50=1-10 μm;
[0021] Preferably, in the first graphite of the first active layer, the secondary particles account for 60% to 90% of the total mass of the first graphite in the first active layer;
[0022] Preferably, the second negative electrode active material further comprises hard carbon. Preferably, the mass content of the hard carbon in the second active layer is 0-10 wt %.
[0023] In a possible implementation, A, B, C, and D satisfy the relationship: 9≥(A*C) / (B*D)≥0.4;
[0024] The positive electrode sheet includes a positive electrode active material, the positive electrode active material includes a transition metal element, and the molar content of Ni in the transition metal element is A%;
[0025] The mass content of silicon in the negative electrode active layer is B wt%;
[0026] The mass content of 1,3,6-hexanetrinitrile in the electrolyte is C wt%;
[0027] The electrolyte further comprises fluoroethylene carbonate, and the mass content of fluoroethylene carbonate in the electrolyte is D wt%;
[0028] Preferably, A is 50-95; B is 3-40; and D is 4-20.
[0029] In a possible implementation, the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes a ternary material Li a Ni x Coy Mn z M b O 2 , 0.5 ≤ x ≤ 0.95, 0 < y < 1, 0 < z < 1, 0.8 ≤ a ≤ 1.2, M is a doping element, 0 ≤ b ≤ 0.05, preferably, 0.001 ≤ b ≤ 0.02; M includes at least one of Al, Mg, Ti, Zr, W, B, P, Nb;
[0030] Preferably, the positive electrode active material further includes lithium cobaltate and / or lithium manganate;
[0031] Preferably, the positive electrode sheet includes a conductive agent, and the conductive agent includes carbon nanotubes.
[0032] In a possible implementation manner, the solvent of the electrolyte includes a cyclic carbonate and a linear carbonate, and the mass ratio of the cyclic carbonate to the linear carbonate is (0.2 - 1):1;
[0033] Preferably, the cyclic carbonate includes at least one of ethylene carbonate (EC), propylene carbonate (PC), and fluoroethylene carbonate (FEC);
[0034] Preferably, the linear carbonate includes at least one of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), and diethyl carbonate (DEC).
[0035] In a possible implementation manner, it satisfies: 3 ≤ X2 / X1 ≤ 8, 0.6 ≤ Y2 / Y1 ≤ 1.4;
[0036] The volume particle size distribution curve of the positive electrode active material is a bimodal curve, the first peak particle size is X1, the second peak particle size is X2, the volume density corresponding to the first peak particle size is Y1, and the volume density corresponding to the second peak particle size is Y2;
[0037] In the bimodal curve, the low peak particle size is the first peak particle size X1, and the high peak is the second peak particle size. Preferably, the range of X1 is: 2 - 8 μm;
[0038] The range of X2 is: 10 - 22 μm.
[0039] In a possible implementation manner, a plurality of negative electrode tabs are provided on one side in the width direction of the negative electrode sheet, and the edge of the negative electrode active layer includes a negative electrode active layer thinning region, and the negative electrode active layer thinning region covers at least a part of the negative electrode tab;
[0040] The width S1 of the negative electrode active layer thinning region and the width S2 of the negative electrode active layer thinning region covering the negative electrode tab satisfy the relationship: 0.05 ≤ S2 / S1 ≤ 0.55.
[0041] In a possible implementation, the positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound to form a winding core, and the winding core includes a plurality of straight areas and a plurality of arc areas;
[0042] The positive electrode sheet extends a positive electrode ear from one side in the width direction of the positive electrode current collector;
[0043] The negative electrode sheet extends a negative electrode ear from one side in the width direction of the negative electrode current collector;
[0044] The positive electrode tab and / or the negative electrode tab are arranged in the straight area.
[0045] In a possible implementation manner, each straight region is provided with a pole ear on one side in the width direction of the positive electrode sheet and / or the negative electrode sheet;
[0046] or
[0047] The positive electrode sheet and / or the negative electrode sheet comprises N straight regions arranged in sequence, wherein 1 / 2N to (N-1) straight regions are provided with a pole ear on one side in the width direction of the positive electrode sheet and / or the negative electrode sheet;
[0048] Preferably, the first straight region and / or the Nth straight region are not provided with pole ears;
[0049] or
[0050] The positive electrode sheet and / or the negative electrode sheet comprises N straight regions arranged in sequence, wherein in the M consecutive straight regions, two pole ears are consecutively arranged every two straight regions, and M≤N-1.
[0051] In a possible implementation, a plurality of positive electrode tabs are disposed on one side of the positive electrode sheet in the width direction, the positive electrode sheet comprises a positive electrode current collector and a positive electrode active layer disposed on at least one surface of the positive electrode current collector, and an edge of one side of the positive electrode active layer close to the positive electrode tab comprises a positive electrode active layer thinning region;
[0052] The positive electrode sheet further includes a ceramic layer, which is located at the edge of the positive electrode sheet close to the positive electrode ear in the width direction of the positive electrode sheet. The width K1 of the ceramic layer and the width K2 of the thinned area of the positive electrode active layer satisfy the relationship:
[0053] 0.2≤K1 / K2≤1.
[0054] The positive electrode sheet includes a positive electrode current collector and a positive electrode active layer arranged on the positive electrode current collector; when preparing the positive electrode active layer, due to the fluidity of the slurry, the coating edge will flow to the adjacent blank area, thereby causing the active layer edge to be thinned, forming a positive electrode active layer thinning area.
[0055] Preferably, the range of K1 is 0.2-2.3 mm; the range of K2 is 2-10 mm.
[0056] The technical solution of the present invention has the following advantages:
[0057] 1. The present invention provides a battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator; the negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer arranged on the negative electrode current collector, the negative electrode active layer comprises a first active layer and a second active layer, and the second active layer is arranged on the surface of the first active layer away from the current collector; the first active layer comprises a first negative electrode active material, and the first negative electrode active material comprises a first graphite; the second active layer comprises a second negative electrode active material, and the second negative electrode active material comprises silicon carbon; the electrolyte comprises 1,3,6-hexane trinitrile, and the mass content of 1,3,6-hexane trinitrile in the electrolyte is 0.5wt% to 10wt%.
[0058] The existing electrolyte system will decompose during the high voltage cycle process, and the decomposition products will continue to deposit on the electrode surface to increase the electrode interface impedance. The electrolyte of the present invention includes 1,3,6-hexane trinitrile (HTCN). The cyano group in the structure of 1,3,6-hexane trinitrile can form a strong interaction with the metal ions on the positive electrode surface to form a stable and uniform positive electrode interface film, which effectively prevents the direct contact between the electrolyte and the positive electrode, thereby reducing the catalytic effect of the metal ions on the electrolyte and avoiding the oxidative decomposition of the electrolyte. At the same time, 1,3,6-hexane trinitrile has three cyano functional groups and has excellent water and acid removal performance. It can effectively remove trace water and HF in the electrolyte, prevent acidic substances from corroding the positive electrode active substance, and can also effectively reduce the probability of side reactions of metal ions dissolved from the positive electrode at the negative electrode, thereby improving the high temperature stability of the battery and further improving the cycle stability and life of the battery. The 1,3,6-hexane trinitrile additive can optimize the interface so that the interfacial film formed by it has the characteristics of low impedance and high stability, thereby also reducing the damage to the interface and material structure during high-temperature cycling.
[0059] The negative electrode active layer includes a first active layer and a second active layer. The second active layer is arranged on the surface of the first active layer away from the current collector, and the second active layer includes silicon carbon. The second active layer is graphite mixed with silicon carbon, and the first active layer is pure graphite. This structure can improve the energy density of the electrode. At the same time, the second active layer contains silicon carbon, which has a large gram capacity and can accommodate more lithium ions, which can reduce lithium precipitation on the surface of the negative electrode during high-rate charging. The volume expansion effect of silicon is large. If the second active layer is in direct contact with the current collector, it will transfer excessive expansion to the negative electrode current collector, causing the extension of the negative electrode current collector, and ultimately causing the extension of the negative electrode sheet, resulting in an increase in the height of the winding core, causing compression of the membrane shell, and corner rupture. The negative electrode active material of the first active layer of the present invention uses pure graphite and does not contain silicon carbon. The first active layer expands less, reducing the volume expansion increase effect of the negative electrode sheet. Reducing the expansion of the first active layer can avoid corner membrane shell rupture of the battery cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0061] Figure 1 1 and 2 are the positive electrode particle size distribution curves of Example 1 and Example C4.
[0062] Figure 2 This is a BSE photo of the cross section of the double-layer coated negative electrode sheet of Example 1;
[0063] Figure 3 The front view (left side) and side view (right side) of the negative electrode sheet;
[0064] Figure 4 The front view (left side) and side view (right side) of the positive electrode sheet;
[0065] Figure 5 This is a schematic diagram of the flattening of the positive electrode sheet of Example 1.
[0066] Reference numerals:
[0067] 1-negative electrode current collector; 2-negative electrode active layer; S1-width of the thinned area of the negative electrode active layer; S2-width of the thinned area of the negative electrode active layer covering the negative electrode ear; 3-positive electrode current collector; 4-positive electrode active layer; K1-width of the ceramic layer; K2-width of the thinned area of the positive electrode active layer; 5-straight area; 6-arc area; 7-positive electrode ear. DETAILED DESCRIPTION
[0068] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0069] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0070] The present invention provides a lithium ion secondary battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator; the negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer arranged on the negative electrode current collector, the negative electrode active layer comprises a first active layer and a second active layer, the second active layer is arranged on the surface of the first active layer away from the current collector; the first active layer comprises a first negative electrode active material, the first negative electrode active material comprises a first graphite; the second active layer comprises a second negative electrode active material, the second negative electrode active material comprises silicon carbon; the electrolyte comprises 1,3,6-hexane trinitrile, the mass content of 1,3,6-hexane trinitrile in the electrolyte is 0.5wt% to 10wt%. Exemplarily, the mass percentage of 1,3,6-hexane trinitrile in the electrolyte is 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%.
[0071] The silicon carbon content of the second active layer is higher than that of the first active layer. Optionally, the mass content of silicon carbon in the first active layer is 0-20wt%, and the mass content of silicon carbon in the second active layer is 10wt%-80wt%. The mass content of silicon carbon in the first active layer can be 0.
[0072] The present invention improves the stability of the positive electrode active material, the stability of the negative electrode sheet, and the stability of the electrolyte lithium salt and the negative electrode film-forming additive by improving the electrolyte and the negative electrode sheet in the lithium ion secondary battery, thereby improving the cycle capacity retention rate of the battery as a whole.
[0073] The negative electrode active layer of the present invention includes a first active layer and a second active layer, the second active layer is arranged on the surface of the first active layer away from the current collector, and the second active layer includes silicon carbon. The negative electrode active layer is arranged in the above manner, which can improve the dynamic performance of the negative electrode sheet while reducing the extension and expansion of the negative electrode sheet; the second active layer includes silicon carbon, which can also improve the gram capacity of the second active layer, reduce the diffusion path of lithium ions, and improve the rate performance and lithium precipitation window.
[0074] The negative electrode sheet doped with silicon carbon will increase the negative electrode potential, which will correspondingly lead to an increase in the positive electrode potential. The increase in the positive electrode potential will make the positive electrode active material more susceptible to irreversible lattice phase change, resulting in metal ion dissolution and gas output. The present invention adds nitrile additives to the electrolyte to stabilize the positive electrode CEI film, protect the positive electrode active material from oxidation, and ensure the stability of the positive electrode active material, thereby better exerting the performance of the second active layer doped with silicon carbon, and overall improving the service life of the battery.
[0075] When nitrile additives are added to the electrolyte, the cyanide group has a strong electronegativity and a strong coordination effect with the transition metal ions in the positive electrode active material, which can inhibit the dissolution of metal ions. Due to its strong electronegativity, nitrile additives can also preferentially capture H when the electrolyte undergoes oxidation side reactions. + , reducing the occurrence of side reactions of the electrolyte. The second active layer is mixed with silicon and carbon, and the first active layer uses pure graphite. This structure can improve the energy density of the negative electrode sheet. At the same time, the second active layer contains silicon and carbon, which has a large gram capacity and can accommodate more lithium ions, which can reduce lithium precipitation on the surface of the negative electrode sheet during high-rate charging. The volume expansion effect of silicon is large. If the second active layer is in direct contact with the negative electrode current collector, it will transfer the excessive expansion to the negative electrode current collector, causing the extension of the negative electrode current collector, and ultimately causing the extension of the negative electrode sheet, resulting in an increase in the height of the winding core, causing compression of the membrane shell, and corner rupture. The pure graphite of the first active layer of the present invention does not contain silicon and carbon, and the expansion of the first active layer is small, which reduces the volume expansion increase effect of the negative electrode sheet. Reducing the expansion of the first active layer can avoid corner membrane shell rupture of the battery cell and improve the cycle performance of the battery.
[0076] In a possible implementation, the particle size D of the active material in the negative electrode active layer is V 50 is L1, the average particle size of silicon carbon in the second active layer is L2, and the O / I value of the second active layer is Z, which satisfies the following relationship: 16≥Z / (L1-L2)≥1.
[0077] The active material in the negative electrode active layer refers to the graphite, silicon carbon and conductive agent remaining after the negative electrode active layer on the negative electrode sheet is washed with water and dried.
[0078] The size of the negative electrode active material affects the kinetic performance, cycle expansion performance, and cycle life of the electrode. The particle size of the active material in the negative electrode active layer is matched with the silicon carbon particle size, which can not only fill the gaps between the graphite particles with silicon carbon, but also increase the surface density of the electrode and reserve expansion space; at the same time, the appropriate particle size is conducive to shortening the transmission distance of lithium ions without causing too many side reactions with the electrolyte. The O / I value of the second active layer reflects the conductivity and expansion of the electrode, and forms a range with the particle size. The electrode within the specified range of the present invention has good physical properties, large surface density, small expansion, and good electrical properties, small polarization, good conductivity, excellent rate performance, and good cycle life. The electrode outside the range has one performance that is better, and one performance will deteriorate.
[0079] Preferably, L1 ranges from 8 to 18 μm; L2 ranges from 6 to 15 μm; and Z ranges from 8 to 30. For example, L1 may be 8 μm, 9 μm, 10 μm, 12 μm, 14 μm, 16 μm, or 18; for example, L2 may be 2 μm, 4 μm, 6 μm, 8 μm, 9 μm, 10 μm, 13 μm, or 15 μm; for example, Z may be 8, 10, 15, 18, 20, 22, 25, or 28.
[0080] In a possible implementation, the second negative electrode active material further includes a second graphite, the second graphite of the second negative electrode active material includes secondary particles, and the first graphite of the first negative electrode active material includes secondary particles and unagglomerated primary particles. The second graphite of the second active layer of the negative electrode sheet is a secondary particle, which can improve the dynamic performance of the battery; the first graphite of the first active layer is a secondary particle mixed with a primary particle, which can improve the compaction and surface density of the first active layer, thereby taking into account both the energy density and rate performance of the negative electrode sheet.
[0081] Preferably, the particle size Dv50 of the secondary particles is 10-20 μm; illustratively, it may be 10 μm, 11 μm, 12 μm, 13 μm, 15 μm, 18 μm or 20 μm.
[0082] Preferably, the particle size of the primary particles is Dv50=1-10 μm; illustratively, it can be 1 μm, 2 μm, 3 μm, 5 μm, 8 μm or 10 μm.
[0083] Preferably, in the first graphite of the first active layer, the secondary particles account for 60wt% to 90wt% of the total mass of the first graphite in the first active layer; illustratively, it may be 60wt%, 70wt%, 80wt% or 90wt%.
[0084] Preferably, the second negative electrode active material also includes hard carbon. Hard carbon has a lithium potential similar to that of graphite and a higher specific capacity. First, hard carbon is composed of a graphite-like microcrystalline structure and open angular microcrystals. This unique microcrystalline structure can not only provide more lithium storage sites, but also facilitate the deintercalation of lithium ions between graphite layers. Graphite has a stable layered structure, which is conducive to the embedding and extraction of lithium ions. And the hard carbon is located in the second active layer, closer to the positive electrode sheet, the lithium ion diffusion distance is short, and the reaction of lithium deintercalation occurs first, which can better play the role of hard carbon. By mixing hard carbon with graphite, the advantages of both can be fully utilized to improve the energy density and power density of the battery. Secondly, although the charge and discharge curve of hard carbon has obvious hysteresis, it has good compatibility with the electrolyte and can exert better electrochemical performance. Although graphite easily reacts with the electrolyte to form an SEI film, its structure is stable, which is conducive to improving the cycle stability of the battery. By mixing, the fast charging performance and cycle stability can be improved, and the volume expansion and structural changes of the battery during the charge and discharge process can be reduced. Finally, hard carbon has good low-temperature and fast-charging performance, high safety, and can prevent battery short-circuit and spontaneous combustion. At the same time, hard carbon is easily passivated and deactivated during thermal runaway, which improves the thermal stability of the battery. This mixed use method can improve the safety and low-temperature performance of the battery and enhance its use effect under various conditions. Preferably, the mass content of the hard carbon in the second active layer is 0 to 10wt%; illustratively, it can be 0, 1wt%, 3wt%, 5wt%, 7wt%, 9wt% or 10wt%.
[0085] In a possible implementation, A, B, C, and D satisfy the relationship: 9≥(A*C) / (B*D)≥0.4;
[0086] The positive electrode sheet includes a positive electrode active material, the positive electrode active material includes a transition metal element, and the molar content of Ni in the transition metal element is A%;
[0087] The mass content of silicon in the negative electrode active layer is Bwt%;
[0088] The mass content of 1,3,6-hexanetrinitrile in the electrolyte is Cwt%;
[0089] The electrolyte further comprises fluoroethylene carbonate, and the mass content of fluoroethylene carbonate in the electrolyte is Dwt%;
[0090] Preferably, A is 50-95; B is 3-40; and D is 4-20.
[0091] Exemplarily, A can be 50, 60, 70, 80, 90 or 95; exemplary, B can be 3, 5, 10, 15, 20, 25, 30, 35 or 40; exemplary, D can be 4, 5, 7, 9, 10, 12, 15, 18 or 20.
[0092] The nickel content of the ternary positive electrode material affects the gram capacity of the material, but the increase in nickel content will reduce the stability of the material. For ternary materials with different nickel contents, by making A, B, C, and D satisfy the relationship: 9≥(A*C) / (B*D)≥0.4, the battery can still maintain the stability of the positive electrode material even when applied to a higher cut-off voltage. The second active layer includes silicon carbon, which can reduce the extension and expansion of the negative electrode sheet while improving the kinetic performance of the negative electrode sheet; the second active layer includes silicon carbon, which can also increase the gram capacity of the second active layer, reduce the diffusion path of lithium ions, and improve the rate performance and lithium precipitation window. Nitrile additives can better ensure the stability of the positive electrode active material, thereby exerting the performance of the second active layer doped with silicon carbon, and overall improving the service life of the battery.
[0093] The Ni element in the ternary material can increase the material's gram capacity, but too high a content will reduce stability and make metal ions dissolve easily. Adding HTCN to the electrolyte can complex with metal ions and form an ICE film, which improves the stability of the positive electrode and electrolyte interface and prevents the electrolyte from oxidative decomposition under high voltage; silicon doping of the negative electrode increases the negative electrode's potential to lithium, and thus also increases the potential of the positive electrode. With the increase in silicon content, the positive electrode active material and electrolyte additives are also optimized accordingly, which can improve the stability and electrical properties of the positive electrode active material. In addition, the addition of FEC can form a stable SEI on the silicon-carbon surface. The amount of silicon added is matched with the corresponding positive electrode active material, and combined with the content of additives in the electrolyte, the cycle stability of the battery system is improved.
[0094] When the nickel content in the positive electrode and the HTCN content in the electrolyte are too high, or the silicon and FEC content in the negative electrode are too low, and (A*C) / (B*D) is greater than 9, the stability of the positive electrode active material will deteriorate, the conductivity of the electrolyte, high-voltage stability and other performance will deteriorate, and the energy density of the battery will decrease on the negative electrode side; when the nickel content in the positive electrode and the HTCN additive content are too low, the positive electrode capacity will decrease, and the stability of the CEI film on the surface of the positive electrode particles will also decrease. The silicon content in the negative electrode is too high, which will lead to a decrease in the stability of the electrode sheet and increased expansion. At the same time, excessive FEC will affect the thermal stability of the positive electrode active material.
[0095] In a possible implementation, the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes a ternary material Li a Ni x Co y Mn z M b O2 where \(0.5\leq x\leq0.95\), \(0\lt y\lt1\), \(0\lt z\lt1\), \(0.8\leq a\leq1.2\), \(M\) is a doping element, \(0\leq b\leq0.05\), preferably \(0.001\leq b\leq0.02\); \(M\) includes at least one of \(Al\), \(Mg\), \(Ti\), \(Zr\), \(W\), \(B\), \(P\), \(Nb\).
[0096] Preferably, the positive electrode active material further includes lithium cobaltate and / or lithium manganate; lithium cobaltate can improve the battery voltage platform, its small particles can improve the rate performance, and its large particles can improve the areal density compaction. Blending lithium cobaltate in the positive electrode active material can improve the battery performance. The mixed use of ternary cathode materials (such as nickel-cobalt-manganese ternary materials) and lithium manganate can have a positive impact on the performance of lithium batteries in multiple aspects. First, this mixed use can significantly reduce the material cost. The cost of lithium manganate is relatively low. Therefore, by mixing lithium manganate with ternary materials, the overall cost can be effectively reduced. Second, blending lithium manganate can improve the safety of the battery. Lithium manganate itself has high structural stability, and after blending, it can help improve the safety performance of the battery, enabling it to better pass safety tests such as针刺 (needle puncture) and overcharge tests. In addition, lithium manganate has excellent rate performance. After mixing with ternary materials, it can improve the rate performance of the battery to a certain extent.
[0097] Preferably, the positive electrode sheet includes a conductive agent, and the conductive agent includes carbon nanotubes. The use of carbon nanotube conductive agents can effectively reduce the internal resistance of the battery, improve the energy density and charge-discharge efficiency of the battery. The one-dimensional tubular structure and small particle size characteristics of carbon nanotubes enable them to form a sufficient conductive network, increase the conductive contact between active substances, improve the electronic conductivity, thereby reducing the contact resistance of the electrode and accelerating the electron movement rate. In addition, compared with traditional conductive agents, carbon nanotubes, as a new type of conductive agent, can achieve the same conductive effect with less addition amount, thereby increasing the content of active substances and further optimizing the battery performance.
[0098] In a possible implementation manner, the solvent of the electrolyte includes cyclic carbonates and chain carbonates, and the ratio of the cyclic carbonate to the chain carbonate is \((0.2 - 1):1\). Cyclic carbonates have good solubility for lithium salts and can improve the stability of the negative electrode surface at the same time. Chain carbonates have a low melting point and viscosity, which can improve the lithium ion conductivity of the electrolyte and enhance the kinetic performance. The two mixed together produce a synergistic effect and expand the electrochemical stability window. When used in combination with high-nickel cathodes and silicon-doped anodes, the formed system has better electrical properties and reduces battery gas generation. Exemplarily, it can be \(0.2:1\), \(0.3:1\), \(0.5:1\), \(0.7:1\) or \(1:1\).
[0099] Preferably, the cyclic carbonate includes at least one of ethylene carbonate (EC), propylene carbonate (PC), and fluoroethylene carbonate (FEC);
[0100] Preferably, the linear carbonate includes at least one of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC) and diethyl carbonate (DEC).
[0101] In a possible implementation, the following conditions are satisfied: 3≤X2 / X1≤8, 0.6≤Y2 / Y1≤1.4;
[0102] The volume particle size distribution curve of the positive electrode active material is a bimodal curve, the first peak particle size is X1, the second peak particle size is X2, the volume density corresponding to the first peak particle size is Y1, and the volume density corresponding to the second peak particle size is Y2;
[0103] like Figure 1 As shown, the abscissa corresponding to the peak with a smaller particle size classification in the bimodal curve is the first peak particle size X1, the abscissa corresponding to the peak with a larger particle size classification is the second peak particle size X2, the ordinate corresponding to X1 is Y1, and the ordinate corresponding to X2 is Y2.
[0104] Preferably, the range of X1 is 2-8 μm, and the range of X2 is 10-22 μm. For example, X1 can be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm or 8 μm, and for example, X2 can be 10 μm, 12 μm, 15 μm, 18 μm, 20 μm or 22 μm.
[0105] In the present invention, the positive electrode active material is graded by large and small particles, and the small particles are single crystal particles, which have the advantages of good stability and good cycle life, but poor rate performance and small compaction of the pole piece; polycrystalline particles are mixed in the pole piece, and the large and small particles are graded, and the small particles are filled in the gaps of the large particles, which can improve the compaction of the pole piece. At the same time, the contact surface between the polycrystalline particles and the electrolyte is larger, and there are more places for lithium ions to be deintercalated, which can improve the rate performance of the positive electrode active material. However, too many polycrystalline particles will cause an increase in side reactions with the electrolyte, increase gas production of the battery cell, and reduce the cycle life. The limited range of particle size and proportion matching in this application can simultaneously ensure the rate performance and cycle performance of the battery.
[0106] In a possible embodiment, a plurality of pole tabs are provided on one side in the width direction of the negative electrode sheet, the edge of the negative electrode active layer includes a negative electrode active layer thinning area, and the negative electrode active layer thinning area covers at least a portion of the pole tab; the width S1 of the negative electrode active layer thinning area and the width S2 of the negative electrode active layer thinning area covering the pole tab satisfy the relationship: 0.05≤S2 / S1≤0.55.
[0107] The “width direction” of the negative electrode sheet refers to the direction along the short side of the negative electrode sheet.
[0108] "Plurality" means two or more.
[0109] Preferably, S1 is 3 to 10 mm, and S2 is 0.2 to 3 mm.
[0110] The negative electrode sheet is double-coated. The difference in viscosity and fineness of the second active layer and the first active layer slurry may cause different fluidity of the slurry. At the edge of the coating, the slurry will flow to the blank area next to it, resulting in thinning of the active layer edge. The N / P ratio decreases when the negative electrode edge is thinned, which brings the risk of edge lithium deposition to the battery. Therefore, cutting the edge thinning area is a low-cost process. The thinning area is retained in the part of the pole ear, and the width of the thinning area of the negative active layer covering the pole ear is the cutting width. Therefore, specifying the thinning area and the cutting width can avoid edge lithium deposition.
[0111] In a possible implementation, the positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound to form a winding core, and the winding core includes a plurality of straight areas and a plurality of arc areas;
[0112] The positive electrode sheet extends a positive electrode ear from one side in the width direction of the positive electrode current collector;
[0113] The negative electrode sheet extends a negative electrode ear from one side in the width direction of the negative electrode current collector;
[0114] The positive electrode tab and / or the negative electrode tab are arranged in the straight area.
[0115] In a possible implementation manner, each straight region is provided with a pole ear on one side in the width direction of the positive electrode sheet and / or the negative electrode sheet;
[0116] or
[0117] The positive electrode sheet and / or the negative electrode sheet comprises N straight regions arranged in sequence, wherein 1 / 2N to (N-1) straight regions are provided with a pole ear on one side in the width direction of the positive electrode sheet and / or the negative electrode sheet;
[0118] or
[0119] The positive electrode sheet and / or the negative electrode sheet comprises N straight regions arranged in sequence, wherein in the M consecutive straight regions, two pole ears are consecutively arranged every two straight regions, and M≤N-1.
[0120] The more pole tabs there are on the electrode sheet, the more conducive it is to current distribution and heat conduction. However, too many pole tabs will affect (1) the overlapping area of the top pole tabs during welding is reduced, the overlapping thickness is increased, the welding difficulty is increased, and over-welding and cold welding are prone to occur; (2) too many pole tabs on the top require too much space in the membrane shell, reducing the energy density of the battery cell; (3) the large number of pole tabs requires more die-cutting times and high costs; (4) the battery cell with more pole tabs is heavier, which reduces the weight energy density.
[0121] The method of the present invention can appropriately reduce the number of tabs and avoid the above problems, but it cannot affect the battery's charge and discharge performance and battery temperature rise. By using the above method, a straight section in the middle separates the tabs, which can maintain the battery's charge and discharge performance, reduce the number of tabs and alleviate the impact of too many tabs, and make the multi-tab battery have better performance. Reduce the space reserved for the tabs to bend at the top, reduce the difficulty of welding the tabs, reduce costs, and increase energy density.
[0122] For example, N=30, M=15, and the starting point of M is the third straight zone, then the first to third, sixth, seventh, tenth, eleventh, fourteenth, fifteenth, and eighteenth to thirty straight zones each extend a pole ear on one side in the width direction of the pole piece;
[0123] For example, N=40, M=10, and the starting point of M is the 29th straight zone. Then, the 1st to 29th, 32nd, 33rd, 36th, 37th, and 40th straight zones respectively extend a pole ear on one side in the width direction of the pole piece (the 1st and Nth straight zones may also not be provided with pole ears).
[0124] In a possible implementation, a plurality of positive electrode tabs are disposed on one side of the positive electrode sheet in the width direction, the positive electrode sheet comprises a positive electrode current collector and a positive electrode active layer disposed on at least one surface of the positive electrode current collector, and an edge of one side of the positive electrode active layer close to the positive electrode tab comprises a positive electrode active layer thinning region;
[0125] The positive electrode sheet further includes a ceramic layer, which is located at the edge of the positive electrode sheet close to the positive electrode ear in the width direction of the positive electrode sheet. The width K1 of the ceramic layer and the width K2 of the thinned area of the positive electrode active layer satisfy the relationship:
[0126] 0.2≤K1 / K2≤1.
[0127] Preferably, the range of K1 is 0.2-2.3 mm; the range of K2 is 2-10 mm.
[0128] The ceramic layer width K1 and the positive electrode active layer thinning area width K2 satisfy 0.2≤K1 / K2≤1 to avoid edge lithium deposition.
[0129] The present invention mixes silicon and carbon into the negative electrode active material and matches it with the battery system to avoid the performance risks brought by the introduction of silicon, including the use of positive and negative electrode active materials, the manufacturing process of the pole pieces, the matching of the diaphragm electrolyte, etc.
[0130] Example 1
[0131] This embodiment provides a lithium-ion secondary battery, including a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator.
[0132] (1) Preparation of positive electrode sheet:
[0133] The ternary NCM90 / 7 / 3, conductive carbon black, carbon nanotubes, and PVDF are stirred into slurry in N-methylpyrrolidone (NMP) at a mass ratio of 95:1:1.5:2.5, and coated, dried, rolled, cut, welded to the tabs, and taped on the positive electrode current collector 3 aluminum foil to prepare the positive electrode sheet. The drying and rolling are conventional steps in the art, and the concentration and coating thickness of the positive electrode slurry can adopt conventional parameters already available in the art.
[0134] (2) Preparation of negative electrode sheet:
[0135] Ingredients for the first active layer: Sodium carboxymethyl cellulose (CMC) is dissolved in deionized water to prepare a gel, and then graphite and carbon black are added to the prepared gel until it is stirred evenly, and finally styrene-butadiene latex (SBR) is added, stirred, and then coated on the copper foil of the negative electrode current collector 1, and then baked, rolled, cut, welded to the pole ear, and pasted with adhesive tape to prepare the negative electrode sheet. The mass ratio of graphite: carbon black: CMC: SBR is 96:1:1.5:1.5.
[0136] Ingredients for the second active layer: Sodium carboxymethyl cellulose (CMC) is dissolved in deionized water to prepare a gel, and then graphite, silicon carbon, carbon nanotubes and acrylic resin (PAA) are added to the prepared gel until it is stirred evenly, and finally styrene butadiene latex (SBR) is added and stirred and then coated on the copper foil, and then baked, rolled, cut, welded to the pole ear, and pasted with adhesive tape to prepare the negative electrode sheet. The mass ratio of graphite: silicon carbon: CMC: PAA: carbon nanotubes: SBR is 66:30:0.5:1.5:1.5:0.5.
[0137] Figure 2 This is a BSE photograph of the cross section of the double-layer coated negative electrode sheet of Example 1, the second active layer is silicon-doped graphite, and the first active layer is pure graphite.
[0138] (3) Electrolyte: solvent preparation, ethylene carbonate (EC): fluoroethylene carbonate (FEC): ethyl methyl carbonate (EMC): diethyl carbonate (DEC) = 2.2:0.8:4:3 by weight (the ratio of cyclic carbonate to chain carbonate is 0.43:1); the concentration of lithium hexafluorophosphate in the electrolyte is 1 mol / L, and the content of 1,3,6-hexanetricarbonitrile in the electrolyte is 2 wt%.
[0139] (4) Diaphragm: A functional diaphragm is used, including a base membrane, a ceramic layer arranged on one side of the base membrane, and an adhesive layer arranged on the ceramic layer and on the other side of the base membrane; the base membrane PE is 5 μm thick, the ceramic layer is boehmite, with a thickness of 2 μm, and the adhesive layer is oil-based PVDF, with a thickness of 2 μm.
[0140] The positive and negative electrodes are separated by a diaphragm, wound into a core, and then encapsulated in an aluminum-plastic film shell. After baking, liquid injection, formation, and secondary sealing, the battery cell is prepared.
[0141] like Figure 5 As shown, the positive electrode sheet of this embodiment includes a straight area 5 and an arc area 6 arranged in sequence. The positive electrode sheet of this embodiment includes 30 straight areas, the graphite of the second active layer is secondary particles, and the graphite of the first active layer is secondary particles mixed with primary particles; the particle size of the secondary particles is Dv50=14.3μm, and the particle size of the primary particles is Dv50=7.6μm; the secondary graphite particles in the first active layer account for 85wt% of the total amount of graphite in the first active layer.
[0142] like Figure 3 , Figure 4 As shown, the width S1 of the thinned region of the negative electrode active layer 2 of this embodiment is 5.5 mm, the width S2 of the thinned region of the negative electrode active layer covering the negative electrode ear is 2.5 mm, and S2 / S1=0.55.
[0143] In this embodiment, a ceramic layer is provided at the edge of the thinned area of the positive electrode active layer 4, the width K1 of the ceramic layer is 2 mm, the width K2 of the thinned area of the positive electrode active layer is 6 mm, and K1 / K2=0.33.
[0144] The rest of the specific parameters are shown in Table 1-Table 4.
[0145] The lithium ion secondary battery of Example A2 is substantially the same as that of Example 1, except that the ternary positive electrode material is NCM50 / 20 / 30, ie, A=50.
[0146] The lithium ion secondary battery of Example A3 is substantially the same as that of Example 1, except that NCM is 70 / 10 / 20, ie, A=70.
[0147] The lithium ion secondary battery of Example A4 is substantially the same as that of Example 1, except that B=3.
[0148] The lithium ion secondary battery of Example A5 is substantially the same as that of Example 1, except that B=40.
[0149] The lithium ion secondary battery of Example A6 is substantially the same as that of Example 1, except that C=1.
[0150] The lithium ion secondary battery of Example A7 is substantially the same as that of Example 1, except that C=10.
[0151] The lithium ion secondary battery of Example A8 is substantially the same as that of Example 1, except that D=4.
[0152] The lithium ion secondary battery of Example A9 is substantially the same as that of Example 1, except that D=20.
[0153] The lithium ion secondary battery of Example A10 is substantially the same as that of Example 1, except that A, B, C, and D are different (see Table 1 for details).
[0154] The molar content of Ni in the transition metal element is A%, the mass content of silicon in the negative electrode active layer 2 is Bwt%, the content of 1,3,6-hexanetricarbonitrile in the electrolyte is Cwt%, and the mass content of fluoroethylene carbonate in the electrolysis is Dwt%.
[0155] The lithium ion secondary battery of Example A11 is substantially the same as that of Example 1, except that A, B, C, and D are different (see Table 1 for details).
[0156] The lithium ion secondary battery of Example A12 is substantially the same as that of Example 1, except that A, B, C, and D are different (see Table 1 for details).
[0157] The lithium ion secondary battery of Example A13 is substantially the same as that of Example 1, except that D is not within the range of 5 to 20 (see Table 1 for details), and does not satisfy 0.4≤A*C / (B*D)≤9.
[0158] The lithium ion secondary battery of Comparative Example 1 is substantially the same as that of Example 1, except that C is not within the range of 0.5 to 10 (see Table 1 for details), and does not satisfy 0.4≤A*C / (B*D)≤9.
[0159] Table 1
[0160]
[0161]
[0162] The lithium ion secondary battery of Example B2 is basically the same as that of Example 1, except that the particle size L1 of the active material in the negative electrode active layer, the average particle size L2 of silicon carbon in the second active layer, and the O / I value Z of the second active layer are different (see Table 2 for details).
[0163] The lithium ion secondary battery of Example B3 is substantially the same as that of Example 1, except that L1, L2, and Z are different (see Table 2 for details).
[0164] The lithium ion secondary battery of Example B4 is substantially the same as that of Example 1, except that L1, L2, and Z are different (see Table 2 for details), and 16≥Z / (L1-L2)≥1 is not satisfied.
[0165] Table 2
[0166] L1 L2 Z 16 ≥ Z / (L1-L2) ≥ 1 Example 1 16.3 8.5 14.6 1.87 Example B2 15.7 7.8 14.2 1.80 Example B3 17.8 10.8 26 3.71 Example B4 13 11.5 30 20
[0167] The lithium ion secondary battery of Example C2 is substantially the same as that of Example 1, except that Y1 and Y2 are different (see Table 3 for details).
[0168] The lithium ion secondary battery of Example C3 is substantially the same as that of Example 1, except that Y1 and Y2 are different (see Table 3 for details).
[0169] The lithium ion secondary battery of Example C4 is substantially the same as that of Example 1, except that X1, X2, Y1, and Y2 are different (see Table 3 for details), and 0.6≤Y2 / Y1≤1.4 is not satisfied.
[0170] The positive electrode particle size distribution curves of Example 1 and Example C4 are shown in Figure 1 The volume particle size distribution curve is a bimodal curve, the low peak particle size is the first peak particle size X1, the high peak particle size is the second peak particle size X2, the volume density corresponding to the first peak particle size is Y1, and the volume density corresponding to the second peak particle size is Y2.
[0171] The lithium ion secondary battery of Example C5 is substantially the same as that of Example 1, except that X1, X2, Y1, and Y2 are different (see Table 3 for details), and do not satisfy 3≤X2 / X1≤8 and 0.6≤Y2 / Y1≤1.4.
[0172] Table 3
[0173]
[0174] The lithium ion secondary battery of Example D2 is substantially the same as that of Example 1, except that the number of positive electrode tabs 7 provided on the positive electrode sheet is different (see Table 4 for details).
[0175] The lithium ion secondary battery of Example D3 is substantially the same as that of Example 1, except that the number of tabs provided on the positive electrode sheet is different (see Table 4 for details).
[0176] The lithium ion secondary battery of Example D4 is substantially the same as that of Example 1, except that the number of tabs provided on the positive electrode sheet is different (see Table 4 for details).
[0177] Table 4
[0178]
[0179]
[0180] The lithium ion secondary battery of Example E2 is substantially the same as that of Example 1, except that the proportions of the components in the electrolyte solvent are different, and the mass ratios of the cyclic carbonate and the chain carbonate are different (see Table 5 for details).
[0181] The lithium ion secondary battery of Example E3 is substantially the same as that of Example 1, except that the proportions of the components in the electrolyte solvent are different, and the mass ratios of the cyclic carbonate and the chain carbonate are different (see Table 5 for details).
[0182] Table 5
[0183] EC FEC EMC DEC Ring vs Chain Example 1 22 8 40 30 0.43:1 Example E2 9 8 40 43 0.2:1 Example E3 25 25 25 25 1:1
[0184] The lithium ion secondary battery of Example F2 is substantially the same as that of Example 1, except that S1 is different (see Table 6 for details).
[0185] The lithium ion secondary battery of Example F3 is substantially the same as that of Example 1, except that S1 is different (see Table 6 for details).
[0186] The lithium ion secondary battery of Example F4 is substantially the same as that of Example 1, except that S2 is different (see Table 6 for details).
[0187] The lithium ion secondary battery of Example F5 is substantially the same as that of Example 1, except that S2 is different (see Table 6 for details).
[0188] S1 is the width of the thinned area of the negative electrode active layer, in mm, and S2 is the width of the thinned area of the negative electrode active layer covering the negative electrode ear, in mm.
[0189] Table 6
[0190] S1 S2 S2 / S1 Example 1 5.5 2.5 0.45 Example F2 10 2.5 0.25 Example F3 8 2.5 0.31 Example F4 5.5 0.5 0.09 Example F5 5.5 0.3 0.05
[0191] The lithium ion secondary battery of Example G2 is substantially the same as that of Example 1, except that K2 is different (see Table 7 for details).
[0192] The lithium ion secondary battery of Example G3 is substantially the same as that of Example 1, except that K2 is different (see Table 7 for details).
[0193] The lithium ion secondary battery of Example G4 is substantially the same as that of Example 1, except that K1 is different (see Table 7 for details).
[0194] The lithium ion secondary battery of Example G5 is substantially the same as that of Example 1, except that K1 and K2 are different (see Table 7 for details).
[0195] Table 7
[0196] K1 K2 K1 / K2 Example 1 2 6 0.33 Example G2 2 10 0.20 Example G3 2 2 1.00 Example G4 1.2 6 0.20 Example G5 0.4 2 0.20
[0197] Example 2
[0198] This embodiment is basically the same as Embodiment 1, except that the negative electrode second active layer slurry includes hard carbon, and the mass ratio of graphite: hard carbon: silicon carbon: CMC: PAA: carbon nanotubes: SBR is 61:5:30:0.5:1.5:1.5:0.5.
[0199] Example 3
[0200] This embodiment is substantially the same as Embodiment 2, except that the mass ratio of graphite: hard carbon: silicon carbon: CMC: PAA: carbon nanotubes: SBR is 56:10:30:0.5:1.5:1.5:0.5.
[0201] Example 4
[0202] This embodiment is basically the same as Embodiment 1, except that the mass ratio of ternary NCM: lithium cobalt oxide: conductive carbon black, carbon nanotubes, and PVDF in the positive electrode slurry is 85:10:1:1.5:2.5.
[0203] Example 5
[0204] This embodiment is basically the same as Embodiment 1, except that the mass ratio of ternary NCM: lithium manganese oxide: conductive carbon black, carbon nanotubes, and PVDF in the positive electrode slurry is 85:10:1:1.5:2.5.
[0205] Test Case
[0206] 1. Parameter test method
[0207] (1) Measurement of nickel content in positive electrode active material: Use ICP to test the Ni, Co, and Mn elements of the positive electrode particles to obtain the ppm mass ratio of the three elements. Divide the PPM mass ratio of the three elements by the amount of the three elements to obtain the molar ratio, and then convert this molar ratio into a percentage. Take the percentage of the nickel element at the end.
[0208] (2) Mass content of silicon in the negative electrode active layer Bwt%: Take 5 g of the negative electrode active layer, weigh W1, and calcine it in a muffle furnace at 800°C for 8 h in an air atmosphere. Take out the remaining material and weigh W2. The ash content is W2 / W1*100%. The ash content is divided by the molar mass of silicon dioxide (60) and then multiplied by the molar mass of silicon (28) to obtain the percentage of silicon in the negative electrode active layer.
[0209] (3) Analysis of electrolyte composition: Use a syringe to extract the electrolyte in the battery and use GC equipment to analyze the component content.
[0210] (4) Particle size D of active material in negative electrode active layer V 50: Wash the negative electrode active layer on the negative electrode sheet with water, dry it and then test it using a laser particle size analyzer.
[0211] (5) Average particle size L2 of silicon carbon in the second active layer: The negative electrode sheet is prepared with a cross-section sample using an argon ion milling device. The SEM test is performed in the backscattering mode and 1K magnification. The particle size of silicon carbon is measured. More than 5 different areas are selected. The particle size of all silicon carbon particles in each area is measured. The total number of particles is not less than 20. The particle size is the farthest distance of the silicon carbon cross-section profile. The average value of all measured particle sizes is taken.
[0212] (6) O / I value test: The negative electrode sheet was cut into sample sheets with an area of 2 cm*2 cm. The XRD test was performed by step scanning with a scanning range of 52-79° and a step width of 0.0131°. The diffraction peak at 2θ=54-55° in the obtained diffraction pattern was the (004) peak of graphite, and its intensity was recorded as I004. The diffraction peak at 2θ=77-78° was the (110) peak of graphite, and its intensity was recorded as I110. The O / I value of the negative electrode sheet was I004 / I110.
[0213] (7) Volume particle size distribution curve of positive electrode active material: Soak the positive electrode sheet in DMC for more than 3 hours to remove the attached substances, and then dry it in a drying room; put the dried positive electrode sheet into a crucible, put it into a muffle furnace, raise the temperature from room temperature to 400°C at 5°C / min, keep it warm for 3 hours, and then cool it to room temperature; take out the calcined positive electrode sheet, brush off the substances on the positive electrode current collector with a brush, and then test it with a laser particle size analyzer.
[0214] (8) Test the thinning area at the edge of the positive and negative electrode sheets using a height gauge to test the middle area of the electrode sheet. Measure 10 points and take the average of the values with a difference of no more than 1 μm, which is recorded as the electrode thickness h1. Test the electrode thickness from the edge of the electrode sheet to the middle. When the difference between the test thickness value and the electrode thickness h1 is less than 1 μm, record the distance from the point to the edge of the active layer as the width of the thinning area.
[0215] The parameter test results are shown in Table 1-Table 7.
[0216] 2. Battery performance test
[0217] (1) Battery 25℃ cycle performance test: Cycle at 25℃, charge at 1C to 4.5V cut-off voltage, charge at constant voltage to 0.05C cut-off current, discharge at 1C to 3V lower limit voltage, and repeat the above charge and discharge 500 times.
[0218] (2) 25°C Cyclic Expansion Rate: Fully charge the battery before cycling and measure the battery thickness B1 before cycling. After 500 cycles, fully charge the battery and measure the cell thickness B2. Expansion rate = (B2-B1) / B1.
[0219] (3) Battery 45°C cycle performance test: Cycle at 45°C, charge at 1C to the cut-off voltage, charge at constant voltage to the cut-off current of 0.05C, discharge at 1C to the lower limit voltage, and repeat the above charge and discharge 300 times.
[0220] (4) 45°C Cyclic Expansion Rate: Fully charge the battery before cycling and measure the battery thickness B1 before cycling. After 300 cycles, fully charge the battery and measure the cell thickness B2. Expansion rate = (B2-B1) / B1.
[0221] (5) 25℃ rate charge: At 25℃, charge at 5C constant current to the upper limit voltage, record the charge capacity R1, then charge at constant voltage to the cutoff current 0.05C, record the charge capacity R2, and the constant current charge ratio is R1 / (R1+R2).
[0222] (6) 25℃ rate discharge: At 25℃, charge and discharge once at 0.2C / 0.2C, and record the discharge capacity R3; charge and discharge once at 0.2C / 5C, and record the discharge capacity R4. The 25℃ rate discharge capacity retention rate = R4 / R3.
[0223] (7) Energy density test method: At 25°C, charge and discharge twice at 0.2C / 0.2C, record the second discharge energy Q, record the weight W of the battery cell, and the energy density ED = Q / W.
[0224] (8) Lithium extraction, cycle battery, and perform dissection and observation after fully charging.
[0225] (9) If there is gas production, observe the next battery cell.
[0226] The battery performance test results are shown in Table 8.
[0227] Table 8
[0228]
[0229]
[0230] From the comparison between the embodiment and comparative example 1, it can be seen that limiting the content of 1,3,6-hexanetricarbonitrile in the electrolyte to within the scope of the present invention can significantly improve the cycle capacity retention rate of the battery.
[0231] From the comparison between Example 1, A2-A12 and Example A13, it can be seen that satisfying 0.4≤A*C / (B*D)≤9 can further improve the cycle capacity retention rate of the battery.
[0232] From the comparison between Example 1, Example B2-B3 and Example B4, it can be seen that satisfying the condition of 16≥Z / (L1-L2)≥1 can further improve the cycle expansion performance of the battery on the basis of improving the battery cycle capacity retention rate.
[0233] By comparing Examples 1, C2-C3 with Examples C4 and C5, it can be seen that satisfying the ranges of 3≤X2 / X1≤8 and 0.6≤Y2 / Y1≤1.4 can further improve the rate performance of the battery on the basis of improving the battery cycle capacity retention rate.
[0234] From the comparison between Example 1 and Example 2, it can be seen that adding hard carbon to the negative electrode can improve the rate performance of the battery to a certain extent.
[0235] By comparing Example 1 with Example D2, it can be seen that when the number of folds of the positive electrode sheet is N and the number of tabs is above 2 / 3N, the rate performance of the battery can be further improved.
[0236] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A lithium ion secondary battery, characterized in that: Including positive electrode sheet, negative electrode sheet, electrolyte and separator; The negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer arranged on the negative electrode current collector, the negative electrode active layer comprises a first active layer and a second active layer arranged on the surface of the negative electrode current collector, and the second active layer is arranged on the surface of the first active layer away from the negative electrode current collector; The first active layer includes a first negative electrode active material, and the first negative electrode active material includes a first graphite; The second active layer includes a second negative electrode active material, and the second negative electrode active material includes silicon carbon; The electrolyte comprises 1,3,6-hexanetrinitrile, and the mass content of 1,3,6-hexanetrinitrile in the electrolyte is 0.5wt% to 10wt%.
2. The lithium ion secondary battery according to claim 1, characterized in that: The particle size D of the active material in the negative electrode active layer V 50 is L1, the average particle size of silicon carbon in the second active layer is L2, and the O / I value of the second active layer is Z, which satisfies the following relationship: 16 ≥ Z / (L1-L2) ≥ 1; Preferably, the range of L1 is 8-18 μm; the range of L2 is 6-15 μm; the range of Z is 8-30.
3. The lithium ion secondary battery according to claim 1, characterized in that: The second negative electrode active material further includes a second graphite, the second graphite in the second active layer includes secondary particles, and the first graphite in the first active layer includes secondary particles and primary particles; Preferably, the particle size of the secondary particles is Dv50=10-20 μm; Preferably, the particle size of the primary particles is Dv50=1-10 μm; Preferably, in the first graphite of the first active layer, the secondary particles account for 60% to 90% of the total mass of the first graphite in the first active layer; Preferably, the second negative electrode active material further comprises hard carbon. Preferably, the mass content of the hard carbon in the second active layer is 0-10 wt %.
4. The lithium ion secondary battery according to any one of claims 1 to 3, characterized in that: A, B, C, and D satisfy the relationship: 9≥(A*C) / (B*D)≥0.4; The positive electrode sheet includes a positive electrode active material, the positive electrode active material includes a transition metal element, and the molar content of Ni in the transition metal element is A%; The mass content of silicon in the negative electrode active layer is Bwt%; The mass content of 1,3,6-hexanetrinitrile in the electrolyte is Cwt%; The electrolyte further comprises fluoroethylene carbonate, and the mass content of fluoroethylene carbonate in the electrolyte is Dwt%; Preferably, A is 50-95; B is 3-40; and D is 4-20.
5. The lithium ion secondary battery according to any one of claims 1 to 4, characterized in that: The positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes a ternary material Li a Ni x Co y Mn z M b O2, where 0.5 ≤ x ≤ 0.95, 0 < y < 1, 0 < z < 1, 0.8 ≤ a ≤ 1.2, M is a doping element, and 0 ≤ b ≤ 0.05; M includes at least one of Al, Mg, Ti, Zr, W, B, P, and Nb; Preferably, the positive electrode active material further comprises lithium cobalt oxide and / or lithium manganese oxide; Preferably, the positive electrode sheet comprises a conductive agent, and the conductive agent comprises carbon nanotubes.
6. The lithium ion secondary battery according to any one of claims 1 to 3, characterized in that: The solvent of the electrolyte includes cyclic carbonate and chain carbonate, and the mass ratio of the cyclic carbonate to the chain carbonate is (0.2-1):1; Preferably, the cyclic carbonate comprises at least one of ethylene carbonate, propylene carbonate and fluoroethylene carbonate; Preferably, the linear carbonate includes at least one of ethyl methyl carbonate, dimethyl carbonate, and diethyl carbonate.
7. The lithium ion secondary battery according to claim 5, characterized in that: Satisfies: 3≤X2 / X1≤8, 0.6≤Y2 / Y1≤1.4; The volume particle size distribution curve of the positive electrode active material is a bimodal curve, the first peak particle size is X1, the second peak particle size is X2, the volume density corresponding to the first peak particle size is Y1, and the volume density corresponding to the second peak particle size is Y2; Preferably, X1 ranges from 2 to 8 μm; Preferably, X2 is in the range of 10 to 22 μm.
8. The lithium ion secondary battery according to any one of claims 1 to 3, characterized in that: A plurality of negative electrode tabs are arranged on one side of the negative electrode sheet in the width direction, the edge of the negative electrode active layer includes a negative electrode active layer thinning area, and the negative electrode active layer thinning area covers at least a portion of the negative electrode tab; The width S1 of the thinned area of the negative electrode active layer and the width S2 of the thinned area of the negative electrode active layer covering the negative electrode ear satisfy the relationship: 0.05≤S2 / S1≤0.
55.
9. The lithium ion secondary battery according to any one of claims 1 to 3, characterized in that: The positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound to form a winding core, and the winding core includes a plurality of straight areas and a plurality of arc areas; The positive electrode sheet extends a positive electrode ear from one side in the width direction of the positive electrode current collector; The negative electrode sheet extends a negative electrode ear from one side in the width direction of the negative electrode current collector; The positive electrode tab and / or the negative electrode tab are arranged in the straight area.
10. The lithium ion secondary battery according to any one of claims 1 to 3, characterized in that: A plurality of positive electrode tabs are arranged on one side of the positive electrode sheet in the width direction, the positive electrode sheet comprises a positive electrode current collector and a positive electrode active layer arranged on at least one side of the positive electrode current collector, and an edge of one side of the positive electrode active layer close to the positive electrode tab comprises a positive electrode active layer thinning area; The positive electrode sheet further includes a ceramic layer, which is located at the edge of the positive electrode sheet close to the positive electrode ear in the width direction of the positive electrode sheet. The width K1 of the ceramic layer and the width K2 of the thinned area of the positive electrode active layer satisfy the relationship: 0.2≤K1 / K2≤1; Preferably, the range of K1 is 0.2-2.3 mm; the range of K2 is 2-10 mm.
Citation Information
Patent Citations
High-voltage lithium ion battery with high-temperature and low-temperature performances
CN112467209A
Lithium ion battery
CN116093415A
Negative plate, electrode assembly, lithium ion battery and electric equipment
CN116598422A
Negative plate and application thereof
CN117133902A
Negative plate and lithium ion battery
CN117374219A
Cited By
Battery cell, battery apparatus, and electric apparatus
WO2026170545A1
Battery cell, battery apparatus, electric apparatus and energy storage apparatus
WO2026208325A1